Public Service Employee Motivation Issues in Georgia - Sakvarelidze, Salome (European Journal of Economics and Business Studies, 2018)
The motivated employee represents the essential condition of any organization’s success. Public and private sector managers should constantly work toward coordinating and increasing employee motivation in order to ensure the timely and effective implementation of the plans set by the organization. Accordingly, proper assessment of processes and prompt determination of individuals’ driving motives are needed. Studies have shown that public service employees from all around the world face challenges, such as: incompatibility of knowledge, experience and position, as well as hard and lightweight work. Consequently, public managers should be aware of modern human resource management methods that can be used in effective and efficient ways to increase employee work quality.The main purpose of the paper is to determine the current situation of the public sector in Georgia. In addition, the research seeks to identify and examine the factors that influence employee demotivation and to determine under what conditions motivation can be a worthwhile investment in a public organizations. Methodologically, the work is based on analysis of the available literature and the results of the research statistically processed based on the survey example of 449 respondents from different Georgian ministries selected by a random simple.
Keywords: Human Resource Management, Motivation, Public Sector Employee, Performance Appraisal, Maslow Hierarchy of Needs.